When Algorithms go Wrong, Who is Liable?. Issue 6 (5th December 2017) - Olhede, Sofia; Wolfe, Patrick
Abstract: As automated decisions affect more and different areas of our lives, we are faced with ethical and legal questions that are likely to change the way we think about algorithms and the law. By Sofia Olhede and Patrick Wolfe